The dynamics of the H+ + D2 reaction: a comparison of quantum mechanical wavepacket, quasi-classical and statistical-quasi-classical results - Jambrina, P. G.; Aoiz, F. J.; Bulut, N.; Smith, Sean C.; Balint-Kurti, G. G.; Hankel, M. (Royal Soc Chemistry, 2010)
A detailed study of the proton exchange reaction H+ + D-2(v = 0, j = 0) -> HD + D+ on its ground 1(1)A' potential energy surface has been carried out using 'exact' close-coupled quantum mechanical wavepacket (WP-EQM), quasi-classical trajectory (QCT), and statistical quasi-classical trajectory (SQCT) calculations for a range of collision energies starting from the reaction threshold to 1.3 eV. The WP-EQM calculations include all total angular momenta up to J(max) = 50, and therefore the various dynamical observables are converged up to 0.6 eV. It has been found that it is necessary to include all Coriolis couplings to obtain reliable converged results. Reaction probabilities obtained using the different methods are thoroughly compared as a function of the total energy for a series of J values. Comparisons are also made of total reaction cross sections as function of the collision energy, and rate constants. In addition, opacity functions, integral cross sections (ICS) and differential cross sections (DCS) are presented at 102 meV, 201.3 meV and 524.6 meV collision energy. The agreement between the three sets of results is only qualitative. The QCT calculations fail to describe the overall reactivity and most of the dynamical observables correctly. At low collision energies, the QCT method is plagued by the lack of conservation of zero point energy, whilst at higher collision energies and/or total angular momenta, the appearance of an effective repulsive potential associated with the centrifugal motion over the well causes a substantial decrease of the reactivity. In turn, the statistical models overestimate the reactivity over the whole range of collision energies as compared with the WP-EQM method. Specifically, at sufficiently high collision energies the reaction cannot be deemed to be statistical and important dynamical effects seem to be present. In general the WP-EQM results lie in between those obtained using the QCT and SQCT methods. One of the main, unexpected, conclusions of this work is that an accurate description of the reaction and of its various dynamical features requires a computationally expensive, accurate quantum mechanical treatment.
Keywords: Potential-Energy Surfaces; Differential Cross-Sections; Classical Trajectory Method; Chemical-Reactions; Reactive Scattering; Collision Complexes; Insertion Reactions; Quantum Dynamics; Reaction System; Charge-Transfer